Public surface disinfection every 2 hours can reduce the infection risk of norovirus in airports up to 83. - Nan Zhang; Linan Zhuang; Marco-Felipe King; Hua Qian; Min Zhu (PLoS Computational Biology)
Norovirus, primarily transmitted via fomite route, poses a significant threat to global public health and the economy. Airports, as critical transportation hubs connecting people from around the world, has high potential risk of norovirus transmission due to large number of public surfaces. A total of 21.3 hours of video episodes were recorded across nine functional areas at the airport, capturing 25,925 touches. A surface transmission model based on a Markov chain was developed. Using the beta-Poisson dose-response model, the infection risk of norovirus and the effectiveness of various interventions in different airports' areas were quantified. Without any preventive measures, restaurants at airports exhibited the highest risk of norovirus transmission, with an infection probability of 8.8×10-3% (95% CI, 1.5×10-3% -2.1×10-2%). This means approximately 4.6 (95% CI, 0.8-10.9) out of 51,494 passengers who entered the restaurants would be infected by an infected passenger. Comparing with no surface disinfection, disinfecting public surfaces every 2 hours can reduce the risk of norovirus infection per visit to the airport by 83.2%. In contrast, comparing with no hand washing, handwashing every 2 hours can reduce the infection risk per visit to the airport by only 2.0%, making public surface disinfection significantly more effective than handwashing. If the mask-wearing rate increases from 0% to 50%, the infection risk of norovirus would be decreased by 48.0% (95% CI, 43.5-52.3%). Furthermore, using antimicrobial copper/copper-nickel alloy coatings for most public surfaces could reduce the infection risk by 15.9%-99.2%.